2019
DOI: 10.1177/2058738419862736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GIT-27NO, a NO-donating compound, on hepatic ischemia/reperfusion injury

Abstract: Hepatic ischemia/reperfusion injury (IRI) is a clinical condition that may lead to cellular injury and organ dysfunction that can be observed in different conditions, such as trauma, shock, liver resection, and transplantation. Moderate levels of nitric oxide (NO) produced by the endothelial isoform of the NO synthase protect against liver IRI. GIT-27NO is a NO-derivative of the toll-like receptor 4 antagonist VGX-1027 that has been shown to possess both antineoplastic and immunomodulatory properties in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…In addition, we also evaluated the transcriptomic analysis of MIF, DDT and their receptors in the brains of a mouse model of alcoholism. This analysis was carried out by DNA microarray analysis that represents a useful in silico toll for the better understanding of pathogenic pathways and the possible prediction of new diagnostic therapeutic approaches in several clinical settings, including immunoinflammatory and autoimmune diseases and fibrotic diseases (45,46,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Our analysis first demonstrated that no differences in the expression of MIF, DDT and their receptors can be found in brains of both rodent models of AUD and patients with this condition.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, we also evaluated the transcriptomic analysis of MIF, DDT and their receptors in the brains of a mouse model of alcoholism. This analysis was carried out by DNA microarray analysis that represents a useful in silico toll for the better understanding of pathogenic pathways and the possible prediction of new diagnostic therapeutic approaches in several clinical settings, including immunoinflammatory and autoimmune diseases and fibrotic diseases (45,46,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Our analysis first demonstrated that no differences in the expression of MIF, DDT and their receptors can be found in brains of both rodent models of AUD and patients with this condition.…”
Section: Discussionmentioning
confidence: 83%
“…After that, the working solution was diluted with serum‐free DMEM. The cells were pretreated with 10 μM of DMF or 5 μM of ML385, 2 h prior to 1,3‐DCP exposure 46,47 …”
Section: Methodsmentioning
confidence: 99%